The Acceptance of Apologies in the Corrective Process: implications for Research and Practice - Strickland, James (Oñati Socio-Legal Series, 2017)
Apology scholars and researchers in psychology, law, and justice commonly conceptualise the corrective process that follows wrongful behaviour as an apology-followed-by-forgiveness sequence. In this paper, however, we suggest on the basis of our analysis of the research literature that a more suitable conceptualisation of the corrective process is one that includes the acceptance of an apology as an additional discrete step that is distinct from forgiveness. We begin with a brief discussion of the psychological view of apologies as a process of negotiation between offending and offended parties, and how psychologists conceive peoples’ responses to apologies. We also review the psychological literature to determine how psychologists define the acceptance of an apology and how they view it within the corrective process. We then briefly examine how the outcome of forgiveness is commonly used as a restorative ideal in the context of restorative justice conferencing and suggest that assessing instead the acceptance of an apology may be more appropriate in this setting. We conclude the paper with a brief agenda for further research.